2019
DOI: 10.1080/17434440.2019.1685870
|View full text |Cite
|
Sign up to set email alerts
|

Leadless cardiac pacing systems: current status and future prospects

Abstract: Introduction: Permanent transvenous pacemaker therapy is an essential management option in patients with symptomatic bradyarrhythmias, but harbors a concomitant risk of serious complications. As most complications are lead-or pocket-related, intracardiac leadless pacemaker therapy has the potential to positively impact patient outcome. Since the first leadless pacemaker implant in 2012, many studies have been conducted to evaluate the effectiveness, safety, and applicability of this novel pacing approach.Areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Contrastingly, patients with LPs have been shown to have superior physical function, mental health, and significantly lower pacemaker-related discomfort [ 9 ]. Indications for leadless pacing include atrioventricular (AV) block with atrial fibrillation, bradycardia, and AV block or sinus node disease that does not require frequent ventricular pacing [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrastingly, patients with LPs have been shown to have superior physical function, mental health, and significantly lower pacemaker-related discomfort [ 9 ]. Indications for leadless pacing include atrioventricular (AV) block with atrial fibrillation, bradycardia, and AV block or sinus node disease that does not require frequent ventricular pacing [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Micra VR can be remotely interrogated via the CareLink system [ 11 ]. It is 1.5 T and 3 T MRI conditionally compatible and allows for rate-responsive pacing and automated pacing capture threshold management [ 1 ]. Furthermore, Reynolds et al demonstrated the Micra VR had significantly fewer major complications compared to a historical cohort of patients that received transvenous pacers [ 2 ].…”
Section: Micra Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2A-N presents the milestones in the evolution of cardiovascular implants and corresponding feasible power strategies over the decades. [19][20][21][22] Emerging cardiovascular Milestones in the cardiovascular implantable devices and corresponding power strategies: Cardiovascular implants: A) first successful pacemaker implantation in 1958; [7] B) the first successful implantation of a left ventricular assist device lasted for 10 days until the patient completed the heart transplant; [19] C) the first ICD was implanted in a patient in 1980; [20] D) the first coronary stent implanted in a patient coronary artery by Sigwart et al in 1986; [21] E) the first leadless pacemaker was implanted in 2012. [22] Power strategies: F) Nikola Tesla achieved inductive power transfer by using a pair of coils in 1889; G) the first far-field wireless microwave transfer was developed in 1964; [191] H) magnetic resonant coupling; [159] I) capacitive coupling; [173] J) mid-field WPT.…”
Section: Continuous Energy Requirement and Power Management In Cimdsmentioning
confidence: 99%